AN INDICATOR CONCEPT FOR MEASURING THE QUALITY OF LIFE IN KAMPUNG KOTA COMMUNITIES IN THE “SMART CITY” - Bagus Nuari Priambudi (Jurnal Pengembangan Kota, 2019)
Kampung Kota is the beginning of the city development with all important aspects and has a special regional characteristic. The sustainability of Kampung Kota is affected by physical development around it. The concept of Semarang city development is in line with the concept of smart cities that trending now. One aspect that a city considers being a Smart City is the quality of life. The study of QoL (Quality of Life) has been increasing and has greatly developed in recent years, especially in large cities throughout the country. But it is not yet reviewed for the indicator concept that used as a measure of the quality of life in Kampung Kota communities. In fact, the problems related to the quality of life of the community is so complex. The research aims to study the indicator to measure the quality of life of the community. The method used in this study is quantitative deductive. The study consists of several stages: (1) content validity study, (2) face validity, (3) test reliability and validity; (4) analysis and conclusions. The results show 5 indicators that can be used as a measure of the quality of life of the people of Kampung Kota in Semarang. The indicators of the physic environmental aspects are safety, comfort, and the roles of the Neighborhood Association (RT/ RW). The indicators of the socio-economic and health aspects are income, environmental health, and availability of public spaces.